SISTEMA MACSA DE MODELAGEM DO APRENDIZ EM AMBIENTES DE ENSINO-APRENDIZAGEM COOPERATIVOS COMPUTADORIZADOS - Teixeira, Cenidalva Miranda de Sousa (2013)
Considering the several important points that motivated the research in the area of computer supported collaborative learning, this PhD thesis gives the state of the art in the area, presents the mathNet system as new Computer Supported Learning Environment that explores the Cooperative Learning paradigm, and proposes the MACSA system for Student Modeling. The mathNet artifact is one of the little software packages that implement effectively the collaborative learning paradigm. It offers new opportunities in education by integrating collaborative learning with computer, multimedia and network technologies in a manner that we believe will challenge traditional methods of pedagogy and benefit the learning process in a fundamental way. The MACSA is implemented as a software agent who aims to handle the information that composes the learner model of MATHNET. In the mathNet Environment the learning process occurs through six cooperative phases: 1) group preparation; 2) knowledge presentation; 3) knowledge assimilation; 4) knowledge application; 5) group evacuation; and 6) individual evaluation. We focus on the information that may be modeled by the agent in asch phase and what this information may be modeled for. Concretely, we will show which information is modeled in the first phase (group preparation) and how it is used for groups formation. The information modeled is made by individual attributes elicited in one moment from questionnaires answered by the students in the first time they use framework, and in other moments from the student system interaction. The MACSA has the originality to integrate quantitative and qualitative metrics to follow and evaluate the student profile and behavior within a teaching-learning session. MACSA administrates the process complexity through software agents and the model was defined based on the questions: what s a model? What to model for? And how to model? MACSA emphasizes the modeling of the interaction within the system during a learning session based on the communication modes and problem resolution phases. Finally, it is presented the representation, organization, implementation, application and integration of MACSA within the MathNet, especially the interaction of the MACSA with the problem resolution agent and all the other agent and all the other agents that made the MathNt agent society.